Chain End‐Functionalized Polymer Brushes with Switchable Fluorescence Response. Issue 5 (3rd January 2019) - Tas, Sinem; Kopec´, Maciej; van der Pol, Rianne; Cirelli, Marco; de Vries, Ilse; Bölükbas, Deniz A.; Tempelman, Kristianne; Benes, Nieck E.; Hempenius, Mark A.; Vancso, G. Julius; de Beer, Sissi
Abstract: Herein is described the switchable fluorescence response of poly(methyl methacrylate) (PMMA) brushes. Chain end fluorescein labeled PMMA brushes are prepared by combining surface‐initiated atom transfer radical polymerization (SI‐ATRP) with a copper‐catalyzed alkyne‐azide cycloaddition (CuAAC) click reaction. Successful attachment of fluorescein is confirmed by measuring fluorescence of the as‐prepared films. Utilizing co‐solvency of PMMA in isopropanol‐water mixtures, responsive behavior of the end‐functionalized brushes is demonstrated by measuring the changes in fluorescence intensity between the swollen and collapsed states. Abstract : Solvent‐dependent switchable fluorescence response of chain end dye labeled poly(methyl methacrylate) (PMMA) brushes is described. Fluorescent dye is attached to the chain end of PMMA brushes with a click reaction. The fluorescent response of the end‐labeled PMMA brush can be switched, utilizing their co‐solvency effect in isopropanol‐water mixtures.